2013
DOI: 10.1007/s40271-013-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Administration and the Impacts of Forgetting a Dose

Abstract: Forgetting or questioning insulin dosing impacts insulin-taking behavior and contributes to patient uncertainty and worry about their diabetes management. Insulin strategies that assist patients in managing memory-related dosing issues may improve adherence or treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…This is in line with a major concerns highlighted by patients (e.g. [3]): remembering what medication has been taken.…”
Section: Tablets)supporting
confidence: 84%
See 1 more Smart Citation
“…This is in line with a major concerns highlighted by patients (e.g. [3]): remembering what medication has been taken.…”
Section: Tablets)supporting
confidence: 84%
“…Taking medications is not just hard work for people who self-manage chronic health conditions [11,9,10,3], it is hard work for everybody.…”
Section: The Work Of Taking Medicationsmentioning
confidence: 99%
“…The inherent complexities of managing insulin, was often an impediment to insulin adherence in several surveys [ 48 , 50 , 62 , 63 ] which reported associations between insulin non-adherence and practical barriers, injection difficulties and regimen inflexibility. Patients remembering whether they had taken their insulin was another factor, with people omitting injections if they were unsure whether they had taken it or not: “I am type 2 and when I forget my insulin in the morning, then I skip it and take my next insulin with my next meal.” [Germany, Male] [ 37 ] …”
Section: Resultsmentioning
confidence: 99%
“…Our finding that HF patients are uncertain about how to handle this situation is consistent with those of others who found that worrying and uncertainty were common in adults with diabetes experiencing insulin dosing problems. 31 Handling a missed dose is clearly a situational skill that needs to be emphasized in teaching sessions.…”
Section: Discussionmentioning
confidence: 99%